1998
DOI: 10.2214/ajr.171.5.9798876
|View full text |Cite
|
Sign up to set email alerts
|

Unicornuate uterus: imaging appearance, associated anomalies, and clinical implications.

Abstract: T he term â€oe¿ unicornuate uterus― is a deceptively simple descriptor of a relatively complex set of mtille nan duct anomalies. Accurate classification using hysterosalpingography, sonography, MR imaging, or a combination of the three techniques requires attention to subtle detail because each technique has its own unique set of findings and limitations. Although as sociated anomalies can be broadly identified with all the subtypes, clinical concerns are type-specific. We describe the characteristics of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 4 publications
0
22
0
2
Order By: Relevance
“…In a case of a noncommunicating horn with functional endometrium, US may also reveal an endometrial collection of blood when this test is performed during menstruation. 16 Although some studies with three-dimensional US examination reported high sensitivity and specificity in showing detailed pelvic anatomy and the uterus itself, MRI is the accepted gold standard in the detection of Mü llerian anomalies. 17,18 A unicornuate uterus appears as a bananashaped structure on axial MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In a case of a noncommunicating horn with functional endometrium, US may also reveal an endometrial collection of blood when this test is performed during menstruation. 16 Although some studies with three-dimensional US examination reported high sensitivity and specificity in showing detailed pelvic anatomy and the uterus itself, MRI is the accepted gold standard in the detection of Mü llerian anomalies. 17,18 A unicornuate uterus appears as a bananashaped structure on axial MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Uterovaginal duplication with obstructed hemivagina accompanied by ipsilateral renal agenesis is a rare entity that is referred to as HerlynWerner-Wunderlich (HWW) syndrome [1]. In all of the cases with HWW syndrome, renal agenesis was located on the same side with the obstruction, and the right side is two times more common than the left [6,7]. As the genital and urinary systems arise from a common ridge of mesoderm, abnormal differentiation of the mesonephric and paramesonephric ducts may cause both uterus and kidney anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…So on 2D USG the presence of rudimentary horn may be helpful to identify unicornuate uterus or may raise a suspicion of unicornuate uterus. 19,20 In two cases 2D USG failed to diagnose unicornuate uterus as there were no rudimentary horns and reported them as normal.…”
Section: 16mentioning
confidence: 99%